Features of power consumption of electrical installations with a DC link - A. V. Petrov; V. E. Martusenko; K. K. Fidiyov; D. I. Sidel'nikov (Вестник Северо-Кавказского федерального университета, 2024)
Introduction. The presence in low-voltage electrical networks of a significant number of electrical appliances with rectifiers determines a sufficiently high level of non-sinusoidality of currents and voltages. This significantly reduces the efficiency of both the network itself and individual consumers sensitive to the spectral composition of the supply voltage. At the same time, a significant part of electrical installations with a DC link requires elimination of ripples at the rectifier output, which, in turn, affects the nature of their power consumption.Goal. Study of dependence of the level of non-sinusoidality of currents consumed by the rectification circuit when feeding a linear load on the degree of voltage ripple smoothing at the rectifier output.Materials and methods. The study is based on the analysis of the spectral composition of the load currents with a rectifier bridge at different capacitance of the smoothing capacitor at the output of the rectifier.Results and discussion. The relationship between the capacitance value of the smoothing capacitor at the output of the bridge rectifier and the shape of the current consumed from the network is determined. A connection was revealed between the level of ripple of the rectified voltage and the degree of non-sinusoidality of the consumed currents.Conclusion. According to the results of the conducted research, it can be concluded that the non-sinusoidal character of power consumption of installations with DC link will be determined not only by the smoothing capacitor capacitance, but also by the load resistance at the output of the rectifier.